INTERNATIONAL LEGAL COOPERATION AND THE PRINCIPLE OF HARMONISATION: LESSONS FROM CROSS-BORDER INSOLVENCY - DOI 10.5935/2448-0517.20200026 - Ghio, Emilie (Juris Poiesis - Qualis A3, 2020)
This project assesses how harmonisation can be promoted and achieved in the EU without a completely uniform legal system in place. The project focuses on international legal cooperation as a means to promote harmonisation throughout the EU. It uses the area of cross-border insolvency law as a case study to investigate the interaction between harmonisation and international legal cooperation. This abstract presents the preliminary hypotheses and some preliminary conclusions of this project.